Open Data and Models for Energy and Environment - Nastasi, Benedetto; Manfren, Massimiliano; Noussan, Michel (MDPI, 2021)
This Special Issue aims at providing recent advancements on open data and models. Energy and environment are the fields of application.For all the aforementioned reasons, we encourage researchers and professionals to share their original works. Topics of primary interest include, but are not limited to:Open data and models for energy sustainability;Open data science and environment applications;Open science and open governance for Sustainable Development Goals;Key performance indicators of data-aware energy modelling, planning and policy;Energy, water and sustainability database for building, district and regional systems; andBest practices and case studies
This is a reprint of articles from the Special Issue published online in the open access journal Energies (ISSN 1996-1073) (available at: www.mdpi.com/journal/energies/special issues/open data energy analytics).
Keywords: Research & information: general; Technology: general issues; Aufsatzsammlung